GERAK MUDRA SULINGGIH SIWA DALAM UPACARA DEWA YADNYA - Ida Bagus Catur Aba Widiatmika; I Made Girinata; I Gede Suwantana (Pangkaja: Jurnal Agama Hindu, 2022)
Sulinggih in carrying out the Mudra sometimes has the same meaning but the form is different. The uniqueness of the mudra movement is strongly influenced by the aguron - guron line. This work descriptively describes Shiva's sulinggih mudra which is practiced during the implementation of Dewa Yadnya. The rhythmic movement of the mudra can carry Sulinggih's soul to Shiva at the time of the Dewa Yadnya ceremony. The stages and forms of mudra have a deep meaning and function, starting from the Akasa Mudra Movement to the Tangkep Hand Movement and the Hredaya Mudra. The energy of the mudra at the time of the dewa yadnya ceremony is able to synergize or synchronize the energies between planets. Spiritually the form and movement of each type of mudra will be related to the form and energy of one of the dewatas as a manifestation of God. Therefore, this mudra energy came to be known as manik secap asta gina, meaning that through the hands everything will be realized. The mudra of Sulinggih Shivat is closely related to Yantra (in the form of offerings), Mantra (puja), and Mudra in the process of purification of the Bhuana Agung.